PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN JOB INSECURITY TERHADAP TURNOVER INTENTION KARYAWAN PT ISKANDAR INDAH PRINTNG TEXTILE DI SURAKARTA - Jumiyati, Suprayitno & Sutarno (Universitas Slamet Riyadi, 2019)
The purpose of this study was to know the effect of job satisfaction, organizational commitment and job insecurity on turnover intention. This study is a survey. The study population is employee PT Iskandar Indah Printing Textile Surakarta. The research sample of 115 people with proportional cluster random sampling technique. Data collection technique used questionnaire, observation and literature. Data were analyzed used multiple linear regression, t-test, F and coefficient of determination. The results showed that the job satisfaction has a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. Job insecurity has a positive and significant effect on turnover intention. Job satisfaction, organizational commitment and job insecurity simultaneously significant effect on turnover intention. The coefficient of determination of the given independent variables are the job satisfaction, organizational commitment and job insecurity to the dependent variable by 92,4% the remaining 7,4% influenced by other factors outside the variables studied.Keywords: job satisfaction, organizational commitment, job insecurity, turnover intention